2019
DOI: 10.4049/jimmunol.1800742
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Monocytes in Acute Alcoholic Hepatitis Are Functionally Activated and Induce IL-17 Expression in CD4+ T Cells

Abstract: In humans, the three main circulating monocyte subsets are defined by their relative cell surface expression of CD14 and CD16. They are all challenging to study because their characteristics are strongly context specific, and this has led to a range of conflicting reports about their function, which is especially so for CD14++CD16+ (intermediate) monocytes. Ex vivo cultures are also often confounded by the concomitant use of immunosuppressive drugs. We therefore sought to characterize the phenotype and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In addition to an activated pro-inflammatory immune response to alcohol, patients with alcoholic hepatitis have evidence of immune dysfunction. The activation of monocytes by gut-derived PAMPs leads to T cell exhaustion with reduced numbers of anti-inflammatory IL-10 producing T cells and functionally impaired monocytes and neutrophils [ 46 , 47 ].…”
Section: Alcohol and The Livermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to an activated pro-inflammatory immune response to alcohol, patients with alcoholic hepatitis have evidence of immune dysfunction. The activation of monocytes by gut-derived PAMPs leads to T cell exhaustion with reduced numbers of anti-inflammatory IL-10 producing T cells and functionally impaired monocytes and neutrophils [ 46 , 47 ].…”
Section: Alcohol and The Livermentioning
confidence: 99%
“…cytes by gut-derived PAMPs leads to T cell exhaustion with reduced numbers of antiinflammatory IL-10 producing T cells and functionally impaired monocytes and neutrophils [46,47].…”
Section: Alcoholic Steatohepatitismentioning
confidence: 99%
“…12 In many autoimmune conditions, I-MCs are enriched 13 and in the context of inflammation drive enhanced memory T-cell proliferation and inflammatory cytokine expression. 14,15 CD16 + MCs from patients with ITP have been shown to specifically promote the expansion of IFNc + CD4 + T cells and concomitantly inhibit the proliferation of Tregs, 16 providing evidence that MCs shape T-cell responses in ITP. However, a detailed MC phenotype in untreated, newly diagnosed patients with active ITP has not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…Human MCs are classified into three subsets based on their cell surface expression of CD14 [lipopolysaccharide (LPS) co‐receptor] and CD16 [activatory Fc gamma receptor III (FcγRIII)] into classical (C‐MCs; CD14 ++ CD16 − ), intermediate (I‐MCs; CD14 ++ CD16 + ) and non‐classical (NC‐MCs; CD14 + CD16 ++ ) MCs 12 . In many autoimmune conditions, I‐MCs are enriched 13 and in the context of inflammation drive enhanced memory T‐cell proliferation and inflammatory cytokine expression 14,15 . CD16 + MCs from patients with ITP have been shown to specifically promote the expansion of IFN‐γ + CD4 + T cells and concomitantly inhibit the proliferation of Tregs, 16 providing evidence that MCs shape T‐cell responses in ITP.…”
mentioning
confidence: 99%
“…Among them, the IL-17 pathway has been observed to upregulate expression in the serum of COVID-19 patients in multiple studies and has been speculated to induce a cytokine storm to promote inflammation, while its inhibitors have been observed to attenuate or even prevent cytokine storms (40). This process has also been reported in the pathogenesis of AH, through intermediate monocytes expansion, functional activation, induction of CD4 T cell IL-17 expression, and enrichment in the liver of AH patients to obtain greater phagocytic capacity (41). Reactom pathway and Wikipathway analysis also found that the common mechanism of AH and COVID-19 exists in pathways such as mediating chemotaxis effects, complementing the first two analyses.…”
Section: Discussionmentioning
confidence: 94%